Revisiting Cultural Aspects of Translation: The Case of “Running in the Family” and “Funny Boy” in French - Gunasekera, Niroshini; Şerban, Adriana (Respectus Philologicus, 2019)
[full article and abstract in English]In this study, we propose to examine some of the challenges and opportunities afforded to the translators by the culturally rich “Running in the Family” (1982) by Michael Ondaatje and “Funny Boy” (1994) by Shyam Selvadurai, through a comparison of the initial texts – which are laden with Sri Lankan cultural content – and their French translations: “Un air de famille” (1991) by Marie-Odile Fortier-Masek and, respectively, “Drôle de garcon” (2000) by Frédéric Limare and Susan Fox-Limare (2000). After a brief discussion of audience design and communication in translation, we focus on the interplay of implicitation and explicitation, drawing on examples from the texts, in particular from the culinary domain. We consider the translators’ options in light of the imperative to design for a new readership and suggest that relevance – which is a matter of degree – is pursued through a mix of choices of unequal suitability.
Keywords: culture; translation; Sri Lanka; Michael Ondaatje; Shyam Selvadurai